Effect of different drying temperatures on the nutritional quality of edible wild mushroom, volvariella volvacea obtained nearby forest areas - Sim Kheng Yuen; Karen Kalianon; Marcus Atong (2014)
This study was conducted to investigate the effect of different drying temperature to the nutritional compositions of edible wild mushroom (Volvariella volvacea) and to determine the best drying temperature suitable for post-harvest handling without compromising their nutritional value. The fresh wild mushroom was obtained from the rural area near to the forest area around Sandakan. The mushroom samples (fresh and treated with 40, 50, 60°C) were tested for proximate analysis (moisture, ash, total crude fibre, fat, protein and carbohydrate content). The fresh mushroom contained high protein (12.38%) and carbohydrate (13.51%); but low in fat content (0.77%) as compared to the commercial one (Lentinus edodes and Agaricus bisporus). All the samples exhibited reducing trend (P<0.05) for the parameters tested (moisture, fat, crude fiber and carbohydrate content) when treated at respective temperatures, except for the ash and crude fiber content. Mushroom treated at 60°C has comparable high energy (1468.73kj) and calorie (346.04kcal) content. The current study revealed that the treatment using 60°C is suitable to dry the edible wild mushroom as it preserves most nutritional values. Future study will focus on the effect of heat treatments to the bioactive components that might present in this edible wild mushroom.